2012
DOI: 10.1063/1.4762004
|View full text |Cite
|
Sign up to set email alerts
|

Optical approaches to improve the photocurrent generation in Cu(In,Ga)Se2 solar cells with absorber thicknesses down to 0.5 μm

Abstract: Electronic properties of the Cu2ZnSn(Se,S)4 absorber layer in solar cells as revealed by admittance spectroscopy and related methods Appl. Phys. Lett. 100, 253905 (2012) Improvement of Voc and Jsc in CuInGaSe2 solar cells using a novel sandwiched CuGa/CuInGa/In precursor structure Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…However, it is demonstrated that high efficiencies (>15%) can only be maintained when the CIGSe absorber is thicker than 1 m [1, 3,7]. One of the dominant reasons is the incomplete absorption of incident light arising from the absorber thickness reduction [1][2][3][4][5], which leads to a much lower current density. Our final goal is to obtain highly efficient ultra-thin CIGSe solar cells (with CIGSe absorber thickness below 500 nm).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it is demonstrated that high efficiencies (>15%) can only be maintained when the CIGSe absorber is thicker than 1 m [1, 3,7]. One of the dominant reasons is the incomplete absorption of incident light arising from the absorber thickness reduction [1][2][3][4][5], which leads to a much lower current density. Our final goal is to obtain highly efficient ultra-thin CIGSe solar cells (with CIGSe absorber thickness below 500 nm).…”
Section: Introductionmentioning
confidence: 98%
“…In the last decade, tremendous attention has been paid to Cu(In,Ga)Se 2 (CIGSe) solar cells with thinner absorbers [1][2][3][4][5][6], which enables the reduction of consumption of rare material indium (In) and resulting manufacturing cost compared to their thick counterparts. However, it is demonstrated that high efficiencies (>15%) can only be maintained when the CIGSe absorber is thicker than 1 m [1, 3,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, this would result in two problems: First, reducing the absorber thickness leads to incomplete absorption of incident photons. According to previous experience in ultrathin CIGSe solar cells, this issue of optical losses can be minimized by improved back contact reflectivity 8,9 and implementation of light trapping, [10][11][12] both of which could be well used in the case of ultrathin CZTS. Second, thinning the absorber makes recombination of minority electrons at the back contact more obvious and quality control more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique thermal, optical, and electrical properties, metallic and dielectric nanoparticles have been studied and applied in various fields such as nano-sensors [1], drug carriers [2,3], nanospectroscopy techniques [4,5], waveguide structures [6,7] and photovoltaics [8]. In recent years, solar cells with thinner absorbers have attracted a lot of attention, due to their reduced consumption of rare material [9,10]. However, the reduction of absorber layer thickness results in the incomplete absorption of incident light, which decreases the photocurrent density.…”
Section: Introductionmentioning
confidence: 99%